A resin solid electrolyte that satisfies both mechanical and electrochemical properties and a preparation method thereof

By mixing and curing wood chips and ionic liquid with epoxy resin, the prepared resin solid electrolyte can meet both mechanical and electrochemical properties, solving the problem of poor performance in the prior art, and achieving efficient structural-energy storage integrated composite material application.

CN118676422BActive Publication Date: 2025-03-25JIANGNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410671829.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-03-25
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

The existing resin solid electrolytes are difficult to take into account both mechanical and electrochemical properties, resulting in limited application in structural-energy storage integrated composite materials.

Method used

The obtained resin solid electrolyte can satisfy both mechanical and electrochemical properties by mixing wood chips and ionic liquid with epoxy resin and curing.

Benefits of technology

The high ionic conductivity and good mechanical properties of the resin solid electrolyte are achieved, the problem of poor performance in the prior art is solved, and the scope of application is expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118676422B_ABST
    Figure CN118676422B_ABST
Patent Text Reader

Abstract

The present invention discloses a resin solid electrolyte that satisfies both mechanical and electrochemical properties and a preparation method, and belongs to the technical field of electrolytes. The method for preparing a resin solid electrolyte that satisfies both mechanical and electrochemical properties described in the present invention comprises the following steps: (1) mixing epoxy resin and curing agent evenly to obtain mixture 1; (2) mixing sawdust and ionic liquid ILE evenly to obtain mixture 2; (3) mixing mixture 1 and mixture 2, curing, and obtaining a resin solid electrolyte. The resin solid electrolyte prepared by the present invention can satisfy both mechanical properties and electrochemical properties, solving the current problem that "mechanical properties and electrochemical properties" cannot be satisfied at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a resin solid electrolyte that satisfies both mechanical and electrochemical properties and a preparation method thereof, belonging to the technical field of electrolytes. Background Art

[0002] The structure-energy storage integrated composite material is a new composite material system that combines energy storage and load-bearing properties, with a resin matrix as a solid electrolyte and conductive fibers as both reinforcement and electrode materials. The structure-energy storage integrated composite material has two core advantages, load-bearing and energy storage, which can effectively reduce system mass, save system space, and improve system efficiency. It has great application potential in the military and civilian fields, and is of great significance for realizing the functionalization, lightweight and high performance of weapons and equipment or aerospace vehicles.

[0003] The structure-energy storage integrated composite material is still in the research and development stage and has not yet been put into practical application. From a technical point of view, the resin solid electrolyte is the key factor affecting the performance of the structure-energy storage integrated composite material. Generally speaking, when the elastic modulus of the resin solid electrolyte reaches 10 9 At the Pa level, its ionic conductivity can only reach 10 -9 S / cm level, the ionic conductivity is relatively low, resulting in low energy storage capacity and poor cycle charge and discharge performance of the structure-energy storage composite material. Therefore, the development of resin solid structure electrolytes with high ionic conductivity is the key to preparing structure-energy storage integrated composite materials with high energy storage capacity and excellent electrochemical performance.

[0004] Solid electrolytes are solid substances with ionic conductivity. These substances provide channels for rapid migration of ions due to point defects in their crystals or their special structures. They have high conductivity at certain temperatures, so they are also called fast ion conductors. The preparation method of conventional resin solid electrolytes is to blend the resin and ionic liquid (for example: literature (Zhang, JM, et al. (2023). "High-strength and machinable load-bearing integrated electrochemical capacitors based on polymeric solid electrolyte." NATURE COMMUNICATIONS 14 (1).)), or to create pores to provide channels for lithium ion transmission (for example: literature (Hu, J., et al. (2021). "Composite polymer electrolytes reinforced by hollow silicananotubes for lithium metal batteries." JOURNAL OF MEMBRANE SCIENCE

[0005] 618.)). However, it is difficult for the resin solid electrolytes prepared by these methods to take into account both mechanical properties and electrochemical properties at the same time. The solid electrolytes with good mechanical properties have poor electrochemical properties, and the resin solid electrolytes with good electrochemical properties have very poor mechanical properties, which limits the application scenarios. Summary of the invention

[0006] [Technical issues]

[0007] It is difficult for existing resin solid electrolytes to simultaneously take into account both mechanical properties and electrochemical properties.

[0008] [Technical solution]

[0009] In order to solve the above problems, the present invention first mixes wood chips and ionic liquid ILE, then mixes with epoxy resin, and solidifies to obtain a resin solid electrolyte. The resin solid electrolyte prepared by the present invention can meet both mechanical and electrochemical properties and has a wider range of applications.

[0010] The first object of the present invention is to provide a method for preparing a resin solid electrolyte that satisfies both mechanical and electrochemical properties, comprising the following steps:

[0011] (1) mixing epoxy resin and curing agent uniformly to obtain a mixture 1;

[0012] (2) mixing the sawdust and the ionic liquid ILE uniformly to obtain a mixture 2;

[0013] (3) Mixture 1 and mixture 2 are mixed and cured to obtain a resin solid electrolyte.

[0014] In one embodiment of the present invention, the epoxy resin in step (1) is bisphenol F type epoxy resin 830.

[0015] In one embodiment of the present invention, the curing agent in step (1) is diethyltoluenediamine (DETDA).

[0016] In one embodiment of the present invention, the mass ratio of epoxy resin to curing agent in step (1) is 3-5:1.

[0017] In one embodiment of the present invention, the uniform mixing in step (1) is performed by stirring at 20-30° C. (room temperature) and 400-800 rpm.

[0018] In one embodiment of the present invention, the preparation method of the ionic liquid ILE in step (2) is as follows:

[0019] 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4), lithium trifluoromethanesulfonate (LIOTF) and propyl carbonate (PC) were uniformly mixed to obtain an ionic liquid ILE;

[0020] Among them, the mass ratio of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4) and lithium trifluoromethanesulfonate (LIOTF) is 4:1;

[0021] The mass ratio of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4) and propyl carbonate (PC) was 100:1;

[0022] The mixture is mixed evenly at 20-30°C (room temperature) and 400-800 rpm for 10-20 hours to completely dissolve lithium trifluoromethanesulfonate (LIOTF).

[0023] In one embodiment of the present invention, the wood chips in step (2) are pine wood chips with a pore size of 200-700 μm.

[0024] In one embodiment of the present invention, the mass ratio of wood chips to ionic liquid ILE in step (2) is 1-3:1.

[0025] In one embodiment of the present invention, the uniform mixing in step (2) is achieved by ultrasonic treatment, so that the ionic liquid can enter the pores of the wood chips; the power of the ultrasound is 30-50 KHz, and the time of the ultrasound is 20-40 min.

[0026] In one embodiment of the present invention, the mass ratio of mixture 1 to mixture 2 in step (3) is 1:1-3.

[0027] In one embodiment of the present invention, after the mixture 1 and the mixture 2 are mixed in step (3), they are poured into a mold for curing, and the size of the mold is selected according to needs.

[0028] In one embodiment of the present invention, in step (3), air bubbles need to be removed after mixture 1 and mixture 2 are mixed but before being poured into a mold.

[0029] In one embodiment of the present invention, the curing in step (3) is performed at 105-115° C. for 1-3 h, at 125-135° C. for 103 h, or at 155-165° C. for 1-3 h.

[0030] In one embodiment of the present invention, the resin solid electrolyte may be immersed in an ionic liquid ILE before use and taken out;

[0031] The immersion is carried out at 20-30°C (room temperature) for 10-30 hours.

[0032] The removal step is to wipe off the excess ionic liquid on the surface.

[0033] The second object of the present invention is the resin solid electrolyte prepared by the method of the present invention.

[0034] The third object of the present invention is to provide a structure-energy storage integrated composite material, which uses the resin solid electrolyte described in the present invention.

[0035] The fourth object of the present invention is the application of the resin solid electrolyte of the present invention in the field of batteries.

[0036] A fifth object of the present invention is to provide a button battery, which is assembled on a packaging machine in the order of negative electrode shell-spring-gasket-resin solid electrolyte-gasket-positive electrode shell to obtain a button battery.

[0037] The sixth object of the present invention is to provide a method for simultaneously improving the mechanical properties and electrochemical properties of a resin solid electrolyte, comprising the following steps:

[0038] (1) mixing epoxy resin and curing agent uniformly to obtain a mixture 1;

[0039] (2) mixing the sawdust and the ionic liquid ILE uniformly to obtain a mixture 2;

[0040] (3) Mixture 1 and mixture 2 are mixed and cured to obtain a resin solid electrolyte.

[0041] [Beneficial Effects]

[0042] (1) The conductivity of the resin solid electrolyte prepared by the method of the present invention is (1.9-5.4)×10 -4 s / cm, tensile strength is 34-41MPa, and Young's modulus is 1.6-1.8GPa.

[0043] (2) The resin solid electrolyte prepared by the present invention can simultaneously meet the requirements of mechanical properties and electrochemical properties, thus solving the current problem that "mechanical properties and electrochemical properties" cannot be met simultaneously. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a physical picture of the resin solid electrolyte prepared in Example 1.

[0045] Figure 2 This is the tensile test specimen of the resin solid electrolyte prepared in Example 1.

[0046] Figure 3 This is the impedance diagram of the resin solid electrolyte prepared in Example 1.

[0047] Figure 4 This is the stress-strain curve of the resin solid electrolyte prepared in Example 1. DETAILED DESCRIPTION

[0048] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0049] The raw materials used in the embodiment:

[0050] Bisphenol F epoxy resin 830: purchased from Nantong Xingchen Synthetic Materials Co., Ltd.

[0051] Curing agent DETDA: purchased from McLean;

[0052] Stirring: Use B13-3 magnetic stirrer;

[0053] Pine sawdust: larch sawdust (specification: 200 mesh, purchased from Senmu Mall, Taobao store); dried in an oven at 70°C for 12 h, and then passed through a series of standard sieves with different mesh sizes to separate them into several particle sizes, with particle sizes of 120, 260, 630, and 700 μm, respectively).

[0054] The preparation method of ionic liquid ILE is as follows:

[0055] 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4), lithium trifluoromethanesulfonate (LIOTF) and propyl carbonate (PC) were stirred at 25°C (room temperature) and 600 rpm for 12 h to completely dissolve lithium trifluoromethanesulfonate (LIOTF) to obtain an ionic liquid ILE;

[0056] Among them, the mass ratio of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4) and lithium trifluoromethanesulfonate (LIOTF) is 4:1;

[0057] The mass ratio of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4) and propyl carbonate (PC) is 100:1.

[0058] Example 1

[0059] A method for preparing a resin solid electrolyte that satisfies both mechanical and electrochemical properties comprises the following steps:

[0060] (1) bisphenol F epoxy resin 830 and curing agent DETDA were stirred at a mass ratio of 4:1 at room temperature (25° C.) and 600 rpm to obtain a mixture 1;

[0061] (2) Pine sawdust (630 μm) and ionic liquid ILE were stirred and mixed in a mass ratio of 2:1, and ultrasonicated at 40 kHz for 30 min to allow the ionic liquid ILE to enter the pores of the pine sawdust, thereby obtaining mixture 2;

[0062] (3) Mixture 1 and mixture 2 were mixed evenly in a mass ratio of 2:1, and vacuumed in a DZF-6030 vacuum drying oven at 50°C for 10 min to remove bubbles, and then injected into a circular mold with a diameter of 16 mm and a height of 1.5 mm, and cured at 110°C for 2 h, 130°C for 2 h, and 160°C for 2 h to obtain a resin solid electrolyte;

[0063] (4) The resin solid electrolyte is immersed in the ionic liquid ILE at room temperature (25° C.) for 12 h, taken out, and the ionic liquid on the surface is wiped off to obtain the immersed resin solid electrolyte.

[0064] Example 2

[0065] A method for preparing a resin solid electrolyte that satisfies both mechanical and electrochemical properties comprises the following steps:

[0066] (1) bisphenol F epoxy resin 830 and curing agent DETDA were stirred at a mass ratio of 4:1 at room temperature (25° C.) and 600 rpm to obtain a mixture 1;

[0067] (2) Pine sawdust (700 μm) and ionic liquid ILE were stirred and mixed in a mass ratio of 2:1, and ultrasonicated at 40 kHz for 30 min to allow the ionic liquid ILE to enter the pores of the pine sawdust, thereby obtaining mixture 2;

[0068] (3) Mixture 1 and mixture 2 were mixed evenly in a mass ratio of 2:1, and vacuumed in a DZF-6030 vacuum drying oven at 50°C for 10 min to remove bubbles, and then injected into a circular mold with a diameter of 16 mm and a height of 1.5 mm, and cured at 110°C for 2 h, 130°C for 2 h, and 160°C for 2 h to obtain a resin solid electrolyte;

[0069] (4) The resin solid electrolyte is immersed in the ionic liquid ILE at room temperature (25° C.) for 12 h, taken out, and the ionic liquid on the surface is wiped off to obtain the immersed resin solid electrolyte.

[0070] Example 3

[0071] A method for preparing a resin solid electrolyte that satisfies both mechanical and electrochemical properties comprises the following steps:

[0072] (1) bisphenol F epoxy resin 830 and curing agent DETDA were stirred uniformly at room temperature (25° C.) and 600 rpm in a mass ratio of 4:1 to obtain a mixture 1;

[0073] (2) Pine sawdust (260 μm) and ionic liquid ILE were stirred and mixed in a mass ratio of 2:1, and ultrasonicated at 40 kHz for 30 min to allow the ionic liquid ILE to be incorporated into the pores of the pine sawdust, thereby obtaining mixture 2;

[0074] (3) Mixture 1 and mixture 2 were mixed evenly in a mass ratio of 2:1, and vacuumed in a DZF-6030 vacuum drying oven at 50°C for 10 min to remove bubbles, and then injected into a circular mold with a diameter of 16 mm and a height of 1.5 mm, and cured at 110°C for 2 h, 130°C for 2 h, and 160°C for 2 h to obtain a resin solid electrolyte;

[0075] (4) The resin solid electrolyte is immersed in the ionic liquid ILE at room temperature (25° C.) for 12 h, taken out, and the ionic liquid on the surface is wiped off to obtain the immersed resin solid electrolyte.

[0076] Comparative Example 1

[0077] A method for preparing a resin solid electrolyte comprises the following steps:

[0078] (1) bisphenol F epoxy resin 830 and curing agent DETDA were stirred at a mass ratio of 4:1 at room temperature (25° C.) and 600 rpm to obtain a mixture 1;

[0079] (2) Pine sawdust (120 μm) and ionic liquid ILE were stirred and mixed in a mass ratio of 2:1, and ultrasonicated at 40 kHz for 30 min to allow the ionic liquid ILE to enter the pores of the pine sawdust, thereby obtaining mixture 2;

[0080] (3) Mixture 1 and mixture 2 were mixed evenly in a mass ratio of 2:1, and vacuumed in a DZF-6030 vacuum drying oven at 50°C for 10 min to remove bubbles, and then injected into a circular mold with a diameter of 16 mm and a height of 1.5 mm, and cured at 110°C for 2 h, 130°C for 2 h, and 160°C for 2 h to obtain a resin solid electrolyte;

[0081] (4) The resin solid electrolyte is immersed in the ionic liquid ILE at room temperature (25° C.) for 12 h, taken out, and the ionic liquid on the surface is wiped off to obtain the immersed resin solid electrolyte.

[0082] The solid electrolyte after impregnation obtained in the embodiment and the comparative example was assembled into a button cell on a manual packaging machine MSK-110 in the order of negative electrode shell-spring-gasket-solid electrolyte after impregnation-gasket-positive electrode shell; the impedance of the button cell was measured by an electrochemical workstation CHI660E;

[0083] The circular mold in step (3) of Examples 1-3 and Comparative Example 1 was replaced with a tensile specimen mold, and the other parts remained unchanged to obtain a mechanical tensile specimen;

[0084] The test results are shown in Table 1;

[0085] It can be seen from Table 1 that the conductivity of the solid electrolyte after impregnation prepared in Examples 1-3 is (1.9-5.4)×10 -4 s / cm, tensile strength is 34-41MPa, and Young's modulus is 1.6-1.8GPa, which can meet both mechanical properties and electrochemical properties. If the particle size of pine sawdust is not appropriate, it is impossible to achieve good electrochemical properties.

[0086] Table 1

[0087] example Pine sawdust pore size / (um) <![CDATA[Ionic conductivity / (S·cm -1 )]]> Tensile strength / (MPa) Young's modulus / (GPa) Example 1 630 <![CDATA[4.29×10 -4 ]]> 35.72 1.79 Example 2 700 <![CDATA[5.32×10 -4 ]]> 34.12 1.63 Example 3 260 <![CDATA[1.94×10 -4 ]]> 40.03 1.80 Comparative Example 1 120 <![CDATA[5.36×10 -5 ]]> 42.31 1.92

[0088] Example 4

[0089] A method for preparing a resin solid electrolyte that satisfies both mechanical and electrochemical properties comprises the following steps:

[0090] (1) bisphenol F epoxy resin 830 and curing agent DETDA were stirred at a mass ratio of 4:1 at room temperature (25° C.) and 600 rpm to obtain a mixture 1;

[0091] (2) Pine sawdust (630 μm) and ionic liquid ILE were stirred and mixed in a mass ratio of 2:1, and ultrasonicated at 40 kHz for 30 min to allow the ionic liquid ILE to enter the pores of the pine sawdust, thereby obtaining mixture 2;

[0092] (3) Mixture 1 and mixture 2 were uniformly mixed in a mass ratio of 2:1, and vacuumed in a DZF-6030 vacuum drying oven at 50°C for 10 min to remove bubbles. The mixture was then injected into a circular mold with a diameter of 16 mm and a height of 1.5 mm, and cured at 110°C for 2 h, 130°C for 2 h, and 160°C for 2 h to obtain a resin solid electrolyte.

[0093] Example 5

[0094] A method for preparing a resin solid electrolyte that satisfies both mechanical and electrochemical properties comprises the following steps:

[0095] (1) bisphenol F epoxy resin 830 and curing agent DETDA were stirred at a mass ratio of 4:1 at room temperature (25° C.) and 600 rpm to obtain a mixture 1;

[0096] (2) Pine sawdust (700 μm) and ionic liquid ILE were stirred and mixed in a mass ratio of 2:1, and ultrasonicated at 40 kHz for 30 min to allow the ionic liquid ILE to enter the pores of the pine sawdust, thereby obtaining mixture 2;

[0097] (3) Mixture 1 and mixture 2 were uniformly mixed in a mass ratio of 2:1, and vacuumed in a DZF-6030 vacuum drying oven at 50°C for 10 min to remove bubbles. The mixture was then injected into a circular mold with a diameter of 16 mm and a height of 1.5 mm, and cured at 110°C for 2 h, 130°C for 2 h, and 160°C for 2 h to obtain a resin solid electrolyte.

[0098] Example 6

[0099] A method for preparing a resin solid electrolyte that satisfies both mechanical and electrochemical properties comprises the following steps:

[0100] (1) bisphenol F epoxy resin 830 and curing agent DETDA were stirred uniformly at room temperature (25° C.) and 600 rpm in a mass ratio of 4:1 to obtain a mixture 1;

[0101] (2) Pine sawdust (260 μm) and ionic liquid ILE were stirred and mixed in a mass ratio of 2:1, and ultrasonicated at 40 kHz for 30 min to allow the ionic liquid ILE to be incorporated into the pores of the pine sawdust, thereby obtaining mixture 2;

[0102] (3) Mixture 1 and mixture 2 were uniformly mixed in a mass ratio of 2:1, and vacuumed in a DZF-6030 vacuum drying oven at 50°C for 10 min to remove bubbles. The mixture was then injected into a circular mold with a diameter of 16 mm and a height of 1.5 mm, and cured at 110°C for 2 h, 130°C for 2 h, and 160°C for 2 h to obtain a resin solid electrolyte.

[0103] Comparative Example 2

[0104] A method for preparing a resin solid electrolyte comprises the following steps:

[0105] (1) bisphenol F epoxy resin 830 and curing agent DETDA were stirred at a mass ratio of 4:1 at room temperature (25° C.) and 600 rpm to obtain a mixture 1;

[0106] (2) Pine sawdust (120 μm) and ionic liquid ILE were stirred and mixed in a mass ratio of 2:1, and ultrasonicated at 40 kHz for 30 min to allow the ionic liquid ILE to enter the pores of the pine sawdust, thereby obtaining mixture 2;

[0107] (3) Mixture 1 and mixture 2 were uniformly mixed in a mass ratio of 2:1, and vacuumed in a DZF-6030 vacuum drying oven at 50°C for 10 min to remove bubbles. The mixture was then injected into a circular mold with a diameter of 16 mm and a height of 1.5 mm, and cured at 110°C for 2 h, 130°C for 2 h, and 160°C for 2 h to obtain a resin solid electrolyte.

[0108] The solid electrolyte obtained in the embodiment and the comparative example was assembled into a button cell on a manual packaging machine MSK-110 in the order of negative electrode shell-spring-gasket-solid electrolyte-gasket-positive electrode shell; the impedance of the button cell was measured using an electrochemical workstation CHI660E;

[0109] The test results are shown in Table 2;

[0110] It can be seen from Table 2 that the conductivity of the solid electrolyte prepared in Examples 4-6 is (1.02-4.21)×10 - 4 s / cm, tensile strength is 34-41MPa, and Young's modulus is 1.6-1.8GPa, which can meet both mechanical properties and electrochemical properties. If the particle size of pine sawdust is not appropriate, it is impossible to achieve good electrochemical properties.

[0111] Table 2

[0112] example Pine sawdust pore size / (um) <![CDATA[Ionic conductivity / (S·cm -1 )]]> Example 4 630 <![CDATA[3.65×10 -4 ]]> Example 5 700 <![CDATA[4.21×10 -4 ]]> Example 6 260 <![CDATA[1.02×10 -4 ]]> Comparative Example 2 120 <![CDATA[3.99×10 -5 ]]>

[0113] Comparative Example 3

[0114] A method for preparing a resin solid electrolyte that satisfies both mechanical and electrochemical properties comprises the following steps:

[0115] (1) bisphenol F epoxy resin 830 and curing agent DETDA were stirred at a mass ratio of 4:1 at room temperature (25° C.) and 600 rpm to obtain a mixture 1;

[0116] (2) mixing the ionic liquid ILE and the mixture 1 in a mass ratio of 50:50 to obtain a mixture 2;

[0117] (3) Mixture 2 was evacuated in a DZF-6030 vacuum drying oven at 50°C for 10 min to remove bubbles, and then injected into a circular mold with a diameter of 16 mm and a height of 1.5 mm. The mixture was cured at 110°C for 2 h, 130°C for 2 h, and 160°C for 2 h to obtain a resin solid electrolyte.

[0118] Comparative Example 4

[0119] A method for preparing a resin solid electrolyte that satisfies both mechanical and electrochemical properties comprises the following steps:

[0120] (1) bisphenol F epoxy resin 830 and curing agent DETDA were stirred at a mass ratio of 4:1 at room temperature (25° C.) and 600 rpm to obtain a mixture 1;

[0121] (2) mixing the ionic liquid ILE and the mixture 1 in a mass ratio of 40:60 to obtain a mixture 2;

[0122] (3) Mixture 2 was evacuated in a DZF-6030 vacuum drying oven at 50°C for 10 min to remove bubbles, and then injected into a circular mold with a diameter of 16 mm and a height of 1.5 mm. The mixture was cured at 110°C for 2 h, 130°C for 2 h, and 160°C for 2 h to obtain a resin solid electrolyte.

[0123] The circular mold in step (3) of comparative examples 3 and 4 was replaced with a tensile specimen mold, and the other parts remained unchanged to obtain a mechanical tensile specimen;

[0124] The test results are shown in Table 3;

[0125] It can be seen from Table 3 that if the ionic liquid is directly added to the resin, it is impossible to take into account both the mechanical and electrochemical properties at the same time.

[0126] Table 3

[0127] example <![CDATA[Ionic conductivity / (S·cm -1 )]]> Tensile strength(MPa) Comparative Example 3 <![CDATA[2.09×10 -5 ]]> 7.36 Comparative Example 4 <![CDATA[1.14×10 -4 ]]> 0.13

[0128] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a resin solid electrolyte that satisfies both mechanical and electrochemical properties, characterized in that: The steps include: (1) mixing epoxy resin and curing agent uniformly to obtain a mixture 1; (2) mixing sawdust and ionic liquid ILE uniformly to obtain mixture 2; wherein the sawdust is pine sawdust with a pore size of 630-700 μm; and the mass ratio of sawdust to ionic liquid ILE is 1-3:1; (3) Mixing mixture 1 and mixture 2, and curing them to obtain a resin solid electrolyte; wherein the mass ratio of mixture 1 to mixture 2 is 1:1-3.

2. The method according to claim 1, characterized in that In step (1), the mass ratio of epoxy resin to curing agent is 3-5:

1.

3. The method according to claim 1, characterized in that In step (1), the epoxy resin is bisphenol F type epoxy resin 830; and the curing agent is diethyltoluenediamine.

4. The method according to claim 1, characterized in that In step (3), curing is performed at 105-115°C for 1-3 hours, at 125-135°C for 103 hours, and at 155-165°C for 1-3 hours.

5. The method according to claim 1, characterized in that The resin solid electrolyte is immersed in the ionic liquid ILE before use and then taken out; wherein the immersion is performed at 20-30° C. for 10-30 hours.

6. A resin solid electrolyte prepared by the method according to any one of claims 1 to 5.

7. A structure-energy storage integrated composite material, characterized in that: The resin solid electrolyte according to claim 6 is used.

8. Use of the resin solid electrolyte according to claim 6 in the field of batteries.

9. A button battery, characterized in that: The button battery is assembled on a packaging machine in the order of negative electrode shell - spring - gasket - resin solid electrolyte according to claim 6 - gasket - positive electrode shell.

10. A method for simultaneously improving the mechanical and electrochemical properties of a resin solid electrolyte, characterized in that: The steps include: (1) mixing epoxy resin and curing agent uniformly to obtain a mixture 1; (2) mixing sawdust and ionic liquid ILE uniformly to obtain mixture 2; wherein the sawdust is pine sawdust with a pore size of 630-700 μm; and the mass ratio of sawdust to ionic liquid ILE is 1-3:1; (3) Mixing mixture 1 and mixture 2, and curing them to obtain a resin solid electrolyte; wherein the mass ratio of mixture 1 to mixture 2 is 1:1-3.

Citation Information

Patent Citations

  • Epoxy-based solid electrolyte with high strength and high ionic conductivity

    CN111600069A

  • Biomass-based solid composite electrolytes for batteries

    US20230006249A1